Study of Knowledge and Compliance at Muhammadiyah Autonomous Organization (ORTOM) on COVID-19 Prevention - Idham Choliq; M. Mundakir; Dede Nasrullah; S. Sukadiono; Vika Ramadhana Fitriyani (Gaster, 2022)
This study was conducted to determine the knowledge and compliance of the COVID-19 pandemic prevention among cadres of Ortom Muhammadiyah in Surabaya. Methods: This study used a cross-sectional design with 315 respondents in the Muhammadiyah autonomous organization in Surabaya. The inclusion criteria in this study included cadres of Ortom Muhammadiyah living in Surabaya aged â‰¥ 18.. Result: Overall from the analysis results, it was found that some respondents (64%) had good knowledge, (31%) had sufficient knowledge, and only (5%) had less knowledge. Whereas in compliance, it was found that most of the respondents (72%) had good compliance, (23%) had sufficient compliance, and only (5%) were less compliance. Conclusions: The majority of Muhammadiyah residents in Surabaya have good knowledge and compliance. This shows that the involvement of organizations in relation to handling COVID-19 is very important, especially the Muhammadiyah organization through its various instruments conducting campaigns and efforts to prevent the spread of COVID-19 in the community.